Inland port vessel emissions inventory based on Ship Traffic Emission Assessment Model–Automatic Identification System. (July 2017) - Zhang, Yan; Gu, Jian; Wang, Wei; Peng, Yiqiang; Wu, Xiaojing; Feng, Xuejun
The designation of ship emission control areas in China evidenced increased attention to ship emissions. Ships calling ports along inland waterways are of particular concern as their emissions exacerbate air pollution in nearby cities. Adapting the Ship Traffic Emission Assessment Model to the local context, this study combines data from Automatic Identification System, vessel profile database, and field investigation results to build a "bottom-up" activity-based inventory of ship emissions. The Nanjing Longtan Container Port was taken as a case study. Results show that total ship emissions for PM10, PM2.5, NOx, SOx, CO, HC, and CO2 in 2014 are 3.45, 2.76, 196.00, 2.90, 20.62, 8.13, and 12, 554.29 t, respectively. Accordingly, ship emission reduction measures were proposed based on the analysis of emission characteristics. The methods and conclusions of the study provide a scientific basis for the inventory and control of the ship emissions in China.